2018
DOI: 10.1103/physreve.97.030102
|View full text |Cite
|
Sign up to set email alerts
|

Glassy phase in quenched disordered crystalline membranes

Abstract: We investigate the flat phase of D-dimensional crystalline membranes embedded in a d-dimensional space and submitted to both metric and curvature quenched disorders using a nonperturbative renormalization group approach. We identify a second-order phase transition controlled by a finite-temperature, finite-disorder fixed point unreachable within the leading order of ε=4-D and 1/d expansions. This critical point divides the flow diagram into two basins of attraction: that associated with the finite-temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 72 publications
4
29
1
Order By: Relevance
“…The conclusion of our work is fourfold. First, we have shown that the longstanding problem of the wrinkling transition taking place in partially polymerized lipid membranes is both qualitatively and quantitatively clarified by means of the NPRG approach used in [3]. Second, reciprocally, this agreement validates the NPRG approach to disordered polymerized and, in particular, consolidates the prediction of the existence of three nontrivial fixed points in the RG flow of the model (1), in contradiction with all previous works.…”
Section: Resultscontrasting
confidence: 67%
See 4 more Smart Citations
“…The conclusion of our work is fourfold. First, we have shown that the longstanding problem of the wrinkling transition taking place in partially polymerized lipid membranes is both qualitatively and quantitatively clarified by means of the NPRG approach used in [3]. Second, reciprocally, this agreement validates the NPRG approach to disordered polymerized and, in particular, consolidates the prediction of the existence of three nontrivial fixed points in the RG flow of the model (1), in contradiction with all previous works.…”
Section: Resultscontrasting
confidence: 67%
“…
The wrinkling transition experimentally identified by Mutz et al[1] and then thoroughly studied by Chaieb et al [2] in partially polymerized lipid membranes is reconsidered. One shows that the features associated with this transition, notably the various scaling behaviors of the height-height correlation functions that have been observed, are qualitatively and quantitatively well described by a recent nonperturbative renormalization group (NPRG) approach to quenched disordered membranes by Coquand et al [3]. As these behaviors are associated with fixed points of RG transformations they are universal and should also be observed in, e.g., defective graphene and graphene-like materials.
…”
supporting
confidence: 53%
See 3 more Smart Citations